The Influence of Financial Inclusion and Financial Technology on the Intention to Use Online Loans: Financial Behavior as an Intervening Variable - Huda, Miftahul; Ajizah, Nur; Nuzil, Nur Rokhmad; Fachruddin, Wiwin (Journal of Ecohumanism, 2024)
This study investigates the influence of financial inclusion and financial technology (fintech) on the intention to use online loans, with financial behavior acting as an intervening variable. In light of the increasing popularity of online loans and the concerns around consumer financial behavior, the research explores how enhanced access to financial services and fintech platforms impacts users’ financial decisions. Using a quantitative design, the study collected data from 150 teachers in Malang Regency through questionnaires and applied path analysis using SPSS 23 to examine the relationships between variables. The results indicate that financial inclusion and fintech significantly improve financial behavior, which, in turn, positively affects the intention to use online loans. The study’s novelty lies in its identification of financial behavior as a key mediator, offering a new model to explain how financial inclusion and fintech shape online loan usage. The findings are particularly valuable for policymakers aiming to improve fintech regulation, platform providers looking to enhance consumer engagement, and educators focusing on financial literacy programs.